New Insights Into Biopesticides: Solid and Liquid Formulations of Essential Oils and Derivatives - López, María D.; Cantó-Tejero, Manuel; Pascual-Villalobos, María J. (Frontiers in Agronomy, 2021)
Essential oils and derivatives have shown effective insecticidal activity against different agricultural pests. However, the use of these bioactive compounds can result in negative effects due to their high volatility and difficult handling. Both solid and liquid formulations of essential oils have been developed in recent years. Currently, there are some commercial products available in the market, but they are still scarce and mainly based on liquid formulations. Solid formulations developed through spray-drying, including complex or micro/nanospheres, present differences in encapsulation efficiency, particle size, and controlled release, depending mainly on wall material or surfactant content. Spray-dried essential oils have clear advantages over liquid formulations in terms of biological protection and storage. However, liquid formulations are usually easier scaled and apply. This review focuses on the advances in both solid and liquid formulations (focusing on nanoemulsions) of essential oils and derivatives in order to allow for their proper use in agriculture.